Separating the Brain Regions Involved in Recollection and Familiarity in Recognition Memory - Yonelinas, Andrew P. (J Neurosci, 2005)
The neural substrates of recognition memory retrieval were examined in a functional magnetic resonance imaging study designed to separate activity related to recollection from that related to continuous variations in familiarity. Across a variety of brain regions, the neural signature of recollection was found to be distinct from familiarity, demonstrating that recollection cannot be attributed to familiarity strength. In the prefrontal cortex, an anterior medial region was related to recollection, but lateral regions, including the anterior and dorsolateral prefrontal cortex, were related to familiarity. Along the lateral parietal cortex, two functionally distinct regions were also observed: a lateral parietal/temporal region related to recollection and a more superior parietal region involved in familiarity. Similarly, in medial parietal regions, the posterior cingulate was related to recollection, whereas the precuneus was related to familiarity. The hippocampus was related to recollection, but also exhibited an inverse relationship to familiarity-driven recognition confidence. The results indicate that recollection and familiarity rely on different networks of brain regions and provide insights into the functional roles of different regions involved in episodic recognition memory.